"That is Terrible News!": Media Framing of Mamba Mentality Within Contemporary U.S. Racial and Gender Politics. (August 2022) - Chen, Ryan; Rochon, M. A.; Anderson, Lauren C.
On January 26, 2020, former Los Angeles Lakers superstar Kobe Bryant passed away suddenly in a helicopter crash. Drawing on theoretical frameworks of racial and gender politics in the U.S. context, and media framing, we conducted a textual analysis of mainstream news media's framing of "Mamba Mentality" in the immediate aftermath of Bryant's death. Across the 119 articles retrieved for analysis, we found Mamba Mentality consistently framed in four ways: a performance standard, both mental and physical; a symbol for overcoming adversity; a commodity; and a legacy/ethos. While mainstream media was complicit in absolving Bryant of his 2003 sexual assault allegation, the allegation was folded into his complex celebrity identity, which ultimately legitimized his Mamba Mentality persona as strong, tough, and able to overcome any obstacle that stood in the way—regardless of the cost. Our findings implicate how a celebrity athlete's life is valued by contemporary media, and how media portrayals represent historical underpinnings of identity politics and oppressive practices, in line with structural and systemic violence in American society.